Illusion in Cultural Practice Productive Deceptions - Rein, Katharina (Taylor & Francis, 2021)
"This volume explores illusionism as a much larger phenomenon than optical illusion, magic shows, or special effects, as a vital part of how we perceive, process, and shape the world we live in. Considering different cultural practices characterised by illusionism, this book suggests a new approach to illusion via media theory. Each of the chapters analyses a specific kind of illusionistic practice and the concept of illusionism it entails in a given context, including philosophy, perception and cognitive theory, performance magic, occultism, optics, physiology, early cinema, cartomancy, spiritualism, architecture, shamanic rituals, and theoretical physics, to show the diversity of shapes that illusionism and illusions can take. The book provides detailed analyses of illusions within performance and ritual magic, philosophy, art history and psychology as well as a first approach to the study of illusions outside of these established fields. It aims to find ways of identifying and analysing a wider range of illusions in the humanities. This multidisciplinary and comprehensive volume will appeal to scholars and students with an interest in media and culture, theatre and performance, philosophy, sociology, politics and religion."